Therapeutic effect and mechanism of different doses of aspirin on preterm delivery in pregnant mice - Xinlan Qu; Xuechun Wu; Xiaomeng Pang; Yuan Fang (PLoS ONE, 2026)
Background Preterm birth is a major cause of perinatal mortality and complications, with inflammation being a key contributing factor. Current treatments, like uterine contraction inhibitors and antibiotics, are unsatisfactory. Aspirin, a cyclooxygenase inhibitor, shows promise in treating infectious preterm labor but has limited in vivo studies and an unclear mechanism. Methods In this study, a mouse model of infectious preterm birth was established via lipopolysaccharide (LPS) injection, and the aspirin doses used in these animals were converted from the recommended human doses by the body surface area method, with the high-dose and low-dose groups set at 0.78 mg/kg and 0.21 mg/kg, respectively. ELISA detected inflammatory factors TNF-α, IL-1β, IL-6 in serum, amniotic fluid and placenta. WST-8 kit and TBA method measured serum SOD activity and MDA content, respectively. DTNB colorimetric method analyzed glutathione content in liver and placenta. Western blot detected MyD88, IκB, p-IκB and nucleus NF-κB p65 protein expression in uterine tissues. Results Results showed the 75 μg/kg LPS group had a 91.7% preterm birth rate and 4.67% stillbirth rate. Low-dose (66.7%) and high-dose (41.6%) aspirin reduced preterm birth and increased live birth rates, with significant intergroup differences (P < 0.05). Aspirin lowered LPS-induced TNF-α, IL-1β, IL-6 in serum, amniotic fluid and placenta, regulated oxidative stress, reversed MyD88/p-IκB overexpression and reduced p65 nuclear translocation. TLR4/NF-κB inhibitors downregulated these factors and nuclear NF-κB p65/p-IκB. Additionally, we found that inflammatory LPS induced abnormal fetal mouse skeletal development (e.g., malformation and deficiency), which was ameliorated by aspirin exposure. Conclusion Aspirin may ameliorate preterm birth by up-regulating TLR4/NF-κB pathway, laying theoretical basis for aspirin clinical application in preterm birth.